Music in the baroque era from Monteverdi to Bach - Bukofzer, Manfred F. 1910-1955 (W. W. Norton & Company, Inc., 1947)
This history of the music of the Baroque Era in Europe--roughly, from the 17th century through the first half of the 18th--covers the entire field, from Monteverdi and Schütz at its inception to the great works of Bach and Handel.--Adapted from publisher description.